Evaluation of the Efficiency of Modified Bone Graft in Putty Consistency in Treatment of Angular Bone Defect - A Pilot Study - Elangovan, Ramnath; Amaladhas, Mejalla Muthiah; Theyagarajan, Ramakrishnan; Pandithurai, Sivaranjani (International Journal of Innovative Research in Medical Science, 2019)
Background: Periodontitis is the inflammatory disease of the periodontium which leads to destruction of the supporting bone and periodontium. Colocast is a bovine derived bone graft. This colocast when processed in a putty consistency constitutes the modified colocast. Aim: The aim is to evaluate the clinical efficiency of consistency modified bone graft material in the treatment of angular bone defects. Materials and Methods: Five patients with angular bone defects were included in this study. Bone defects were treated with bone grafts in putty consistency. Probing depth, clinical attachment level along with mesial and distal bone level were evaluated at baseline and three months after surgery. Results: There was a clinically and statistically considerable Probing depth reduction, Clinical Attachment Level gain and increase in bone formation at both mesial and distal aspect of treated teeth. Conclusions: The Modified bone graft in putty consistency has been proven to be effective in managing angular bone defects along with ease at handling the graft in this study.